Taphonomic analysis and Paleobiological Observations of Crossvallia unienwillia Tambussi et al. 2005, the oldest Penguin from Antarctica - Acosta Hospitaleche, Carolina Ileana Alicia; Pérez, Leandro Martín; Marenssi, Sergio Alfredo; Reguero, Marcelo Alfredo (Ameghiniana)
The purpose of this paper is to provide a taphonomic analysis of the holotype of Crossvallia unienwillia Tambussi, Reguero, Marenssi and Santillana, 2005, in order to improve the knowledge of the vertebrate record of the Cross Valley Formation, a unit exposed in the central area of Marambio (Seymour) Island, Antarctic Peninsula. Analyses of the preservational state of the skeleton assigned to Crossvallia unienwillia offer important data for palaeoenvironmental and depositional reconstructions, key for the understanding of the early evolutionary history of penguins. Different techniques, including petrographic sections, SEM observation, Secondary Electrons Detectors, backscattered electrons detectors, microanalysis for probe of electrons, and X-ray diffraction were applied in order to distinguish biostratinomic from fossil diagenetic damage. Fossil bones of Crossvallia are associated with a typical marine assemblage including shark remains and macroinvertebrates. The hosting mudstones suggest a low-energy environment either below the wave-base or protected from wave action. In any case initial marine conditions changed to other with regular influx of land-derived sedimentary material. Crossvallia unienwillia was a female diver that passed through several molting periods before death. Biostratinomic processes consistent with little transport and rapid burial which would have prevented the action of destructive processes such as weathering and carnivores or scavenging, are inferred. The rapid burial favored the initial preservation of the elements under anoxic conditions. The surficial corrosion, fractures, and the internal filling of the cavities, suggest that destructive processes were only important after final burial during the telodiagenetic stage. The absence of more vertebrate fossil remains in the Cross Valley C Allomember is the result of those destructive processes, whereas on the contrary the original depositional environment appears to have been optimal. El objetivo de este trabajo es el análisis ...